Evaluation of albumin –cobalt binding as a specific test for assessment of myocardial infarction. - Al-Ghamber, Mohammed Fawzi; Razzak, Khalil Bekri A.; Al-Shamma, Ghassan A. (Journal of the Faculty of Medicine Baghdad, 2007)
Background : The new biological marker, ischemia modified albumin (IMA) measured by albumin cobalt binding (ACB) test was introduced for the detection of myocardial ischemia.Objective The aim of the present study was to describe the performance characteristics of the ACB test in suspected acute coronary syndrome patients who presented to the emergencydepartment early after the onset of ischemic events and to verify the specificity of the test for myocardial infarction.Subjects and methods: Forty five patients presented to the emergency department (ED) with chest pain and 31 healthy controls were involved in the study. Serum albumin and ACB test were performed on all subjects, while serum CK-MB was done on patients with chest pain only. The patients were diagnosed to have either myocardial infarction, MI (30) or unstable angina, UA ( 15 ). The sensitivity and specificity of the ACB test for the detection of ischemia were evaluated by ROC curve analysis.Results and conclusion ACB test could be considered as an early test for myocardial ischemia and could detect ischemia much earlier than other cardiac markers. The significant negativepredictive value of the test may play an important role in the rapid rule out of myocardial ischemia and will reduce the inappropriate admission of low risk patients. However it is a poordiscriminator between patients with MI and those with UA.